Editorial: Begin, Again. Issue 1 (11th February 2016) - RAE, PAUL
Abstract : This is my first issue as senior editor of Theatre Research International . That the journal and I are almost exactly the same age is at once thrilling and a little unsettling. One feels both the weight of tradition, and the sense of mission and possibility that contemporaries can share. Indeed, looking through back issues, I am struck by how integrally TRI has both reflected and driven changes in performance practice and scholarship that I recognize from my own intellectual development. I began my undergraduate studies at Bristol University Drama Department – publisher, from 1959 to 1974, of one of TRI 's two precursors, New Theatre Magazine (the other being Theatre Research/Recherches théâtrales ). That was in 1992, in the same year an editorial by Claude Schumacher highlighted a reorientation of the journal away from text-based drama towards 'the theory of theatre practice'. I left the UK to make theatre (and a life) in Singapore in 1996, just as the journal began notably to expand its international scope. And I commenced my PhD on cosmopolitanism and performance in 2001, at the same time as Brian Singleton's overhaul of the journal's structure and focus set the internationalizing standard for the publication that exists today. That year, I made my first trip to Australia, to present on a panel for emerging scholars at a conference of the International Federation for Theatre Research (IFTR, the organization with which this publication is affiliated), hosted by the University of New South Wales. Subsequent conference participation brought me into contact with TRI editors Christopher Balme, Freddie Rokem, Elaine Aston and Charlotte Canning, and, courtesy of the IFTR member's subscription, the material they were publishing.